Perfusion brain imaging with SPECT- technique German Guideline S1 - Kranert, T.; Menzel, C.; Bartenstein, P.; Brust, P.; Coenen, H. H.; Krause, B. J.; Kuwert, T.; Sabri, O.; Schreckenberger, M.; Tatsch, K.; Grünwald, F. (Nuklearmedizin - NuclearMedicine, 2013)
This paper describes the guideline for perfusion brain imaging with SPECT-technique published by the Association of the Scientific Medical Societies in Germany (AWMF). The purpose of this guideline is to provide practical assistance for indication, examination procedures, findings and their interpretation also reflecting the present state of the art. Information and instruction are given regarding indication, preparation of the patients and examination procedures of brain perfusion SPECT, including preparation and quality control of the tracer as well as the radiation dosimetry, technical performance of image acquisition with the gamma-camera and image processing. Also advices for interpretation of findings are given. In addition, possible pitfalls are described.
Keywords: Brain perfusion; SPECT; HMPAO; ECD